2021
DOI: 10.3389/fcell.2021.687024
|View full text |Cite
|
Sign up to set email alerts
|

Fexofenadine Protects Against Intervertebral Disc Degeneration Through TNF Signaling

Abstract: Objective: Fexofenadine (FFD) is an antihistamine drug with an anti-inflammatory effect. The intervertebral disc (IVD) degeneration process is involved in inflammation in which tumor necrosis factor-α (TNF-α) plays an important role. This study aims to investigate the role of FFD in the pathological process of IVD degeneration.Methods: Safranin O staining was used for the measurement of cartilageous tissue in the disc. Hematoxylin-Eosin (H&E) staining was used to determine the disc construction. A rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Moreover, to further explore the biological functions of OSIDDRGs, we performed the function enrichment analysis and identified several crucial KEGG pathways which might be involved in IDD. In fact, several of these identified signaling pathways have been verified in IDD, including TNF signaling pathway [45], estrogen signaling pathway [7], MAPK signaling pathway [46], HIF-1 signaling pathway [47], Toll-like receptor signaling pathway [48], and glutathione metabolism [49]. However, how the OSIDDRGs participate in IDD via these signaling pathways has not been fully understood and needs the further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, to further explore the biological functions of OSIDDRGs, we performed the function enrichment analysis and identified several crucial KEGG pathways which might be involved in IDD. In fact, several of these identified signaling pathways have been verified in IDD, including TNF signaling pathway [45], estrogen signaling pathway [7], MAPK signaling pathway [46], HIF-1 signaling pathway [47], Toll-like receptor signaling pathway [48], and glutathione metabolism [49]. However, how the OSIDDRGs participate in IDD via these signaling pathways has not been fully understood and needs the further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that elevated expression of inflammatory cytokines is a critical factor leading to IVDD ( Liu K. et al, 2021 ). To investigate the role of scutellarin in the progression of the inflammatory response during IVDD, primary human nucleus pulposus cells (HNPCs) were isolated and then cultured with TNF-α in the presence or absence of scutellarin for 24 h to detect the mRNA level and 48 h to detect the protein level of inflammatory biomarkers.…”
Section: Resultsmentioning
confidence: 99%
“…TNF-α has been shown to be associated with a variety of pathological IDD processes such as inflammatory cascade, ROS production, apoptosis, ECM degradation, pyroptosis and proliferation. These indicate their critical role in the development of IVDD [25,26]. Additionally, it can also induce an inflammatory response in the nucleus pulposus, leading to an increase of iNOS and COX2 and acceleration of intervertebral disc destruction [27].…”
Section: Discussionmentioning
confidence: 99%